Performance Index Analysis on the Construction of Probolinggo - Banyuwangi Toll Road Package 3 - Sholikhah, Ummatus; Teki Tjendani, Hanie; Wulandari, Esti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the performance index of the Probolinggo-Banyuwangi Toll Road Package 3 construction project using the Earned Value Method (EVM) to evaluate time and cost performance. Infrastructure projects, particularly toll roads, play a vital role in enhancing regional connectivity and economic growth. However, large-scale construction projects frequently face challenges such as cost overruns and delays. The Earned Value Method provides a comprehensive framework for measuring project performance by comparing planned costs, actual expenditures, and completed work. This research employs key performance indicators, including Budgeted Cost of Work Scheduled (BCWS), Budgeted Cost of Work Performed (BCWP), and Actual Cost of Work Performed (ACWP), to determine the Schedule Performance Index (SPI) and Cost Performance Index (CPI). The findings reveal that the project experienced schedule delays, with an SPI of 0.93, indicating that work progress was behind the planned schedule. However, the project maintained cost efficiency, as shown by a CPI of 1.06, reflecting lower actual costs than budgeted. The study highlights the importance of continuous performance monitoring using EVM to identify potential risks, optimize resource allocation, and support timely decision-making. The results provide valuable insights for project managers to improve efficiency and ensure project success in large-scale infrastructure developments.